A randomized controlled double dummy parallel group clinical trial on the efficacy of laser light delivered by a laser pointer device for the relief of pain from acute muscular strain using mefenamic acid as comparator - Ampil, Isaac David E.
Introduction: Laser therapy is a local pain modality in the treatment of acute muscular strain that can prevent the risks of hypersensitivity and side effects associated with systemic analgesic drugs. However, it is expensive and not locally available. The laser pointer device uses the same wavelength of laser light used in pain therapy, is relatively cheap and is widely available. Preliminary evidence of efficacy was observed in previous uncontrolled pilot study of 34 consecutive patients with musculoskeletal diseases whose baseline VAS pain scores decreased after local light application using a laser pointer. Objective: This study aimed to determine the efficacy of laser light delivered by a laser pointer device in relieving the pain of acute muscular strain compared to oral Mefenamic acid in sodium lauryl sulfate formulation (Postan SF, Pfizer) in terms of the amount of pain relief as measured by modified Visual Analogue Scare (VAS). The other objects were to compare the duration of pain relief as well as to describe the adverse events experienced by patients in the laser pointer therapy and Mefenamic acid treatment groups after 30 days of follow-up.
Methods: This randomized, single-blind, double-dummy (placebo), controlled clinical trial included adult patients with acute mild to moderate pain from muscle strain of an extremity in the outpatient clinic, emergency room, investigators' clinic, charity ward or pay floors of the University of the East-Ramon Magsaysay Memorial Medical Center from August 1, 2002 to December 31, 2004. For the experimental group, laser light was applied locally for 5 minutes using a laser pointer device, and a dummy oral drug (empty capsule) was given. For the control group, dummy light and 500 mg of oral Mefenamic acid capsule is sodium lauryl sulfate formulation (Ponstan SF, Pfizer) were administered. VAS pain we scores were monitored at baseline, at the 5th minute, and 1, 2, 4 and 8 hours after treatment. The changes in pain scores from baseline were calculated by taking the difference between baseline VAS and Final VAS, where final VAS was either the VAS score at the 8th hour post-treatment, or the VAS score before a subject was given the rescue medicine, sublingual Piroxicam (Fedline Flash, Pfizer). In addition, the duration of pain relief was calculated from the time when VAS score increased by at least 5 mm from the previous VAS determination minus the time of onset initial pain relief. Adverse events were also monitored during the 30-day observation period and then described per group.
Results: Of 152 eligible subjects, two refused to participate due to the prolonged 8-hour observation period required, leaving a total of 150 patients randomized to either of the 2 study groups, 75 for the laser group and 75 for the Mefenamic group. Baseline characteristics of the groups were comparable. Two (2) patients in the laser group and 5 in the control group had no clinically significant decrease in pain after treatment, necessitating a shift to Piroxicam. Nineteen (19) patients in the laser group and 23 in the control group had total pain relief after treatment but could no longer wait for the completion of the 8-hour observation period; these 42 patients were subsequently monitored by telephone. Intent to treat analysis was done using the method of last observation carried forward with the last VAS score as the final VAS score for dropouts, missing data and patients shifted to Piroxicam. Analysis showed a non-clinically significant difference in the change of pain score between the two treatment groups: mean of 37.0mm, SD=12.5, min-max=0-62 for the laser group; and mean of 37.8 mm, SD=12.4, min-max=0-62 for the control group. This was also not statistically significant (p value=0.4586, t-test). The difference between the two groups was 0.8 (95% CI: 0.7 to 1.0).
The duration of pain relief could not be adequately assessed because they were only 2 cases of pain recurrence; 1 patient per group. The time to onset of pain recurrence for the patient in the laser group was 8 hours while the time for the patient in the control group was 4 hours. There were2 cases of mild epigastric discomfort for the control group resulting in an adverse event rate of 2.7% (95% CI=0.3-9.3). There were no adverse events reported in the laser group (95%CI=0-4.8). Conclusion: Laser therapy as delivered by a laser pointer device produces the same amount of analgesia as Mefenamic in relieving the mild to moderate pain of acute muscle strain. The exact duration was not established but is longer than 8 hours. There were no adverse events observed using the later pointer after 3 days of follow-up.
Thesis (MS Clinical Epidemiology)--University of the Philippines Manila
Keywords: Lasers in medicine; Pain treatment; Mefenamic acid